Short courses of mechanical ventilation with high-O-2 levels in elderly rat lungs - Cavassani, Samia Santos; Campos Junqueira, Virginia Berlanga; Moraes, Juliana Britto; Luzo, Karen Kristina; Assis Silva, Claudeny Matos; Barros, Maciel; Marinho, Márcia [UNESP]; Simoes, Ricardo Santos; Oliveira-Junior, Itamar Souza (Acta Cirúrgica Brasileira, 2011)
Purpose: To evaluate the effects of mechanical ventilation (MV) of high-oxygen concentration in pulmonary dysfunction in adult and elderly rats. Methods: Twenty-eight adult (A) and elderly (E), male rats were ventilated for 1 hour (G-AV1 and G-EV1) or for 3 hours (G-AV3 and G-EV3). A and E groups received a tidal volume of 7 mL/kg, a positive end-expiratory pressure of 5 cm H2O, respiratory rate of 70 cycles per minute, and an inspiratory fraction of oxygen of 1. We evaluated total protein content and malondialdehyde in bronchoalveolar lavages (BAL) and performed lung histomorphometrical analyses. Results: In G-EV1 animals, total protein in BAL was higher (33.0 +/- 1.9 mu g/mL) compared with G-AV1 (23.0 +/- 2.0 mu g/mL). Upon 180 minutes of MV, malondialdehyde levels increased in elderly (G-EV3) compared with adult (G-AV3) groups. Malondialdehyde and total proteins in BAL after 3 hours of MV were higher in elderly group than in adults. In G-EV3 group we observed alveolar septa dilatation and significative increase in neutrofiles number in relation to adult group at 60 and 180 minutes on MV. Conclusion: A higher fraction of inspired oxygen in short courses of mechanical ventilation ameliorates the parameters studied in elderly lungs.

OBJETIVO: Avaliar os efeitos da ventilação mecânica com alta concentração de oxigênio em animais adultos e idosos. MÉTODOS: Vinte e oito ratos machos (adultos e idosos; n=7 por grupo) foram divididos em ventilados por 1 hora (G-AV1 e G-EV1) e ventilados por 3 horas (G-AV3 e G-EV3). Os grupos receberam volume corrente de 7 mL/kg, pressão positive ao final da expiração de 5 cmH2O, frequência respiratória de 70 ciclos por minuto e fração inspirada de oxigênio de 100%. Ao final do experimento avaliamos no lavado brônquio-alveolar as proteínas totais, malondialdeído, celularidade e a histomorfometria do parênquima pulmonar. RESULTADOS: Em animais idosos ventilados por 1 hora (G-EV1) as proteínas totais no lavado brônquio-alveolar aumentaram (33.0±1.9 µg/mL) quando comparados com os adultos (G-AV1; 23.0±2.0 µg/mL). Após 180 minutos de ventilação mecânica os níveis de malondialdeído e as proteínas totais estavam elevadas nos animais idosos (G-EV3) quando comparadas com os adultos (G-AV3; p<0.001). No grupo de animais idosos (G-EV3) observamos ainda dilatação dos septos alveolares e aumento significativo no número de neutrófilos em relação aos adultos ventilados, tanto aos 60 quanto aos 180 minutos de ventilação mecânica (p<0.001). CONCLUSÃO: A ventilação mecânica com alta fração inspirada de oxigênio por um curto período de tempo favoreceu os parâmetros pulmonares estudados nos animais idosos.
Ventilação mecânica de curta duração com altos níveis de O2 em pulmões de ratos idosos
Keywords: Aging; Lung injury; Ventilator-Induced Lung Injury; Neutrophil Infiltration; Oxidative Stress; Rats